Analysis of the Jerez-Xérès-Sherry and Manzanilla de Sanlúcar de Barrameda Wines Market in the Period 1982-2012. - Rodríguez-García, Juan; Vieira-Rodríguez, Áurea (Revista de Estudios Andaluces, 2017)
The Jerez-Xérès-Sherry and Manzanilla de Sanlúcar de Barrameda wines are one of the most famous world wide forits peculiar method of production, forits different types and forits quality. They have been the most exported wines from Spain during the nineteenth century and most of the twentieth. They have occupied a prominent place in the Spanish trade balance in the nineteenth century. One of the most relevant characteristics of these wines is their exporting vocation, with the foreign market being their main destination. Currently, Jerez wines export more than 70% of their production, with the UK, Holland and Germany being their main markets, apart from being present in almost a hundred countries. In the present article we analysis commercial evolution and its trends in its main markets in the period between 1982 and 2012. We also point out and analysis causes of its decline and the different restructuring plans put in place to balance supply and demand and also face the process of globalization of the international wine market to gain foreign market shares.